Health of war-affected Karen adults 5 years post-resettlement. (22nd January 2021) - Hoffman, Sarah J; Shannon, Patricia J; Horn, Tonya L; Letts, James; Mathiason, Michelle A
Abstract: Background: An estimated 140 000 refugees from Burma have resettled to the USA since 2009, comprising 21% of total resettlement in the USA over the last decade. Our objective was to describe patterns of longitudinal health outcomes in a cohort of Karen refugees resettled in the USA for 5 years, and to translate these findings to a primary healthcare context. Methods: The study was a retrospective cohort study focused on the analysis of the first 5 years of electronic health records of a sample of 143 Karen refugees who were initially resettled between May 2011 and May 2013. Results: Through descriptive, inferential and survival statistics, we described patterns of retention in primary care, biometric trends, condition prevalence and survival probabilities. Highest prevalence health conditions documented at any point in the 5-year period included diagnoses or symptoms associated with pain (52%); gastrointestinal disturbance (41%); metabolic disorder (41%); infectious process (34%); mental health condition (31%) and central nervous system disorder (24%). Conclusions: This study is the first retrospective longitudinal analysis of patterns of health in Karen refugees originating from Burma and resettled to the USA. Findings identified in the 5-year, the post-resettlement period provided important clinical insights into the health trajectories of war-affected populations. Burden of illness was high although results did not demonstrate the extent of trauma-associated physical health conditions reported in the literature. Indicators such as significant increases in body mass index (BMI), the overall prevalence of dyslipidaemia and others suggested that the cohort may be exhibiting an early trajectory towards the development of these conditions. Authors summarize potential protective factors experienced by the cohort that promoted aspects of health frequently challenged in forced migration.